Out of sight out of mind. - Lim, Chin Ping. (2009)
Out of Sight Out of Mind is a photojournalism project that documents the lives of mental patients housed in rehabilitation homes. The report highlights the thought processes and challenges faced in different phases of the project, from basic research to actual shooting to the production of a photo journal. It also covers insights on the issue of mental illness and stigma in Singapore.